Analisis Faktor yang Mempengaruhi Konsumen untuk Keputusan Membeli di Rumah Potong Hewan Padil Pratama Kota Palopo - Mirsan Mirsan; Naimah Haruna; Hamja Abd Malik; Burhanuddin Harahap (Penerbit Goodwood, 2024)
Purpose: The Slaughterhouse (RPH), is generally known by the community as a place to slaughter cows and buffaloes or also called large ruminants, this place is usually to slaughter cows and buffaloes for meat. Methodology/approach: This study is designed as descriptive research with an explanatory quantitative approach, studies the variables observed descriptively, and analyzes the influence that occurs between dependent variables on independent variables. The dependent variable consists of the purchase decision (Y), while the independent variable consists of consumption (X1), meat price (X2), location (X3) Results/findings: Results obtained the study found that the influence of the consumption variable is a positive and significant effect on the purchase decision at RPH Padil Pratama Palopo City, the influence of the price variable of the yield obtained meat did not have a positive and significant effect on the purchase decision at RPH Padil Pratama Palopo City, the influence of the variable location of the results obtained had a positive and significant effect on the decision to buy at RPH Padil Pratama Palopo City. Limitations: The analysis in this study still requires additional in-depth variables, such as marketing mix and loyalty, to obtain more in-depth measurement results. Contribution: The theoretical implications of this study underscore the importance of maintaining consumer loyalty to meat consumption in RPH Padil Pratama.